Altered solid and liquid gastric emptying in patients with duodenal ulcer disease. Issue 7 (July 1985) - Maddern, G J; Horowitz, M; Hetzel, D J; Jamieson, G G
Abstract : Alteration in gastric emptying has been implicated in duodenal ulcer disease. The precise abnormalities remain controversial. We have used a radionuclide technique to assess solid and liquid gastric emptying in 14 patients with endoscopically proven duodenal ulcer and 22 healthy controls. Solid gastric emptying values for the patient group fell within the normal range. The median time taken for 50% (T50) of the liquid marker to empty from the stomach was 12 minutes (range 6-23 minutes) which was significantly faster (p less than .005) than controls (median 18 minutes, range 11-35). In 10 of the 14 patients, however, the rate of liquid emptying was within the normal range. There was no significant difference in the T50 for gastric emptying of solids between the groups, but in duodenal ulcer patients food left the stomach significantly earlier than in controls (p less than .05). After this, however, the linear rate at which duodenal ulcer patients emptied solid food from the stomach was a median 0.75%/minutes (range 0.5-1.4 minutes), which was slower (p less than .0005) than controls, median 1.25/minutes (range 0.7-2.3). These results show that the pattern of gastric emptying of digestible solids and liquids in patients with duodenal ulcer disease, as a group, is significantly altered.